The perception of non-economics and business major students towards the compulsory entrepreneurship course: Have the learning outcomes of the course been achieved? - Kusumawati, Fiska; Santosa, Cecep Anwar Hadi Firdos; Hasibuan, Heni Yunilda (Universitas Wiralodra, 2023)
Entrepreneurship contributes to economic growth, making it an important factor in advancing society and the economy in the present time. The significance of innovation and entrepreneurship in the current era necessitates that the younger generation understands the subject. This understanding can be achieved through entrepreneurship courses offered in higher education. Based on this, several universities have implemented policies that make entrepreneurship courses mandatory for all students. This research aims to explore in-depth the perception of students, specifically those not majoring in economics, management, business, or social sciences, regarding the entrepreneurship course and the university policy regarding the requirement to take it. The study adopts a qualitative approach using focus group discussion (FGD). The researcher, along with five students from the same university, discusses the learning outcomes of the Innovation and Entrepreneurship course and the university policy regarding the mandatory nature of the course. The FGD generates several points related to the learning outcomes of the course. These include students' ability to comprehend the concepts and principles of entrepreneurship, their ability to generate ideas for business creation, their capacity to develop innovative business plans, and the appropriateness of making the Innovation and Entrepreneurship course mandatory as it benefits all students, including those not majoring in economics, management, business, or social sciences.